Aquatic microdrile Oligochaeta (Annelida, Clitellata): New nominal taxa and combinations since 1984 - Timm, Tarmo (Zootaxa, 2017)
This is a catalogue of 1081 new nominal taxa and 372 new combinations or names with new ranks of available scientific names given to the oligochaetes in freshwater and marine families that have been described since the publication of the monograph by Brinkhurst & Jamieson (1971) and its supplement (Brinkhurst & Wetzel 1984). Eight names are listed for the family Alluroididae, seven for the Capilloventridae, 26 for the Haplotaxidae, 144 for the Lumbriculidae, 75 for the Naididae, two for the Opistocystidae, 11 for the Parvidrilidae, 51 for the Phreodrilidae, 34 for the Pristinidae, six for the Randiellidae, one for the Tiguassidae, and 1088 for the Tubificidae. In the Propappidae and the Narapidae there are no new names or combinations subsequent to 1984. Families with predominantly terrestrial species are excluded from this paper. More than half of the species-group names, 54.4%, belong to marine taxa.